Doppler indices of superior thyroid artery in clinically euthyroid adults - Joish, Upendra Kumar; Kavitha, Y; Reddy, R Harikiran; Prabhu, Anitha S; Kumar, M Chetan; Siddharth, M C (Indian Journal of Radiology and Imaging, 2018)
Context: Ultrasonography of thyroid gland is a frequently performed investigation. Many of the diffuse thyroid pathologies are associated with altered vascularity. In view of potential applications and scant available data, there is a need to find normal values of Doppler indices of superior thyroid artery (STA). Aims: To find the normal range of Doppler indices like mean peak systolic velocity (PSV), resistivity index (RI), and pulsatility index (PI) of STA in clinically euthyroid adult individuals. Settings and Design: Prospective cross-sectional observational study. Materials and Methods: A study was done in the Department of Radiodiagnosis of a tertiary care hospital, involving clinically euthyroid adult volunteers. Ultrasonography of the thyroid gland with Doppler of bilateral STAs was performed and mean values of PSV, RI, and PI were calculated. Results: A total of 208 subjects, with a mean age of 37.7 years, underwent Doppler evaluation of STA; 148 of them were women and 60 were men. The mean PSV obtained was 16.94 ± 5.3 cm/s. Mean PI and RI were 0.93 ± 0.31 and 0.5 ± 0.13, respectively. There was no significant difference in the values obtained among both the genders. Conclusion: Mean values of Doppler indices of STA in euthyroid individuals have been found in this study.
Keywords: Peak systolic velocity; pulsatility index; resistivity index; superior thyroid artery; thyroid function